The Comprehensive Agrarian Reform Program and Coase theorem - Fabella, Raul V. (The Philippine Review of Economics, 2003)
The prohibition of the sale or usufruct of land under the Comprehensive Agrarian Reform Law has, in effect, destroyed the legal rural land market and, in its wake, the legal rural credit market. These markets have gone underground resulting in very high transactions cost and threatened bankruptcy to farmers. Section 27 of CARL contravenes an efficiency result in economics called the Coase theorem. Reforms suggested are analyzed in light of this theorem.